Valuation of the rustic farm "La Laguna" in Tierra Blanca, province of Cartago: An Integral Proposal - Álvarez-Varela, Diana (2017)
An analysis of different methods used in appraisal was carried out, with the objective of finding the physical value of a farm in Tierra Blanca de Cartago, dedicated to the cultivation of onions, potatoes and beets, and with an area of 6,347.31 m2. The research estimated the value of land using three different methods, econometric, comparative and financial, and for the valuation of infrastructure located on the farm, the net cost of replacement method was used. For the econometric method, land in nearby communities was searched for a total sample of 17 land price references, and the econometric model was run, taking as reference the size of the land and the distance to the development center, which in this case, Is the city of Carthage. The proposed econometric method estimated a value of ¢ 10,911.55 / m2, while the comparative method based on 6 selected references, estimated the value of the land is ¢ 9,355.65 / m2. These results were close to that obtained by the financial method which estimated a value of ¢ 8,483.44 / m2 for the land under rotational use of potato and onion. The final value of the land was obtained as an average of the three previous methods and was of ¢ 9,583.55 / m2 for a total land value of ¢ 60,829,762.75. The cost of buildings provided a state of conservation of 0.9794, an age of 38 years, a useful life of 45 years, the value of waste is 0 and a new value of replacement per square meter of ¢ 74,440.72 and a value Total of the building of ¢ 2.274.816,58.